THE POPULATION AND DISTRIBUTION OF AGARWOOD PRODUCING TREE (AQUILARIA MALACCENSIS) IN RIAU PROVINCE - Yulizah Yulizah; Joeni Setijo Rahajoe; Agusdin Dharma Fefirenta; Agung Adi Nugroho (BRIN Publishing (Penerbit BRIN), 2022)
YULIZAH, RAHAJOE, J. S., FEFIRENTA, A. D. & NUGROHO, A. D. 2022. The population and distribution of agarwood producing tree (Aquilaria malaccensis) in Riau Province. Reinwardtia 21(1): 1–11. — Riau Province is one of the largest agarwood producers and supplier of Aquilaria malaccensis species in Indonesia, based on the data of trade quota that was issued by the Ministry of Environment and Forestry in 2018. The quota data will be used for monitoring the sustainability of the population agarwood producing trees in the wild. The aimed of the study were to determine the natural population distribution and habitat preference of wild agarwood-producing trees in Riau Province. The agarwood population census carried out by making random plots in the study sites, soil moisture, soil pH, temperature and the humidity recorded, and the macronutrients data also used to support the habitat preferences for the agarwood producing taxa tree. Seven locations of agarwood producing trees were selected for the study sites including Taman Hutan Raya (TAHURA: Forest Park Garden) Sultan Syarif Hasyim (SSH), three community forests in Siak Sri Indapura District (Gosib, Perincit and Dosan), and three community forests in Bengkalis District (Langkat, Pangkalan Jambi, and Duri Km 13). The density of agarwood producing trees in TAHURA SSH recorded for about 38 plants ha-1, with an average diameter distribution was 15 cm, and the tree height was 9.51 m. Perincit data showed the highest density, with 8.13 plants ha-1 with an average distribution of tree diameters was recorded for 20.8 cm and the tree height was 9.11 m. While the lowest tree density was recorded for 0.58 plant ha-1 in Gosib, the average diameter and tree height were recorded for 40.15 cm and 14.70 m, respectively. Environmental parameters and soil chemistry were the main factors to support the tree growth of agarwood. The result was necessary for the conservation program of A. Malaccensis, and support data for providing potential seeds source and seedling. The nutrient content preference from the finding of this research will also be used as the necessary information of the needs of nutrient content in the natural habitat of agarwood plantations.